Omnibus Law as Investment Law Reform in Indonesia Based on the Hierarchy of Legislation Principles - Sujono, Imam; Nugroho, Mulyanto (Journal of Progressive Law and Legal Studies, 2023)
This paper aims to describe, understand and analyze the omnibus law as an investment law reform in Indonesia based on the hierarchical principle of laws and regulations. As for writing this article using normative legal research. In addition, the writing of this article uses a theoretical and juridical approach. The results of this study indicate that in the formation of the omnibus law as a rule that facilitates Indonesian investment, the hierarchical principle of laws and regulations applies. Then there is some urgency to form an omnibus law in the investment aspect. One of the theories of the welfare state that applies to Indonesia is the role of increasing the economy in the investment sector through the omnibus law in order to realize the mandate of the Indonesian constitution, namely to promote general welfare and as much as possible for the prosperity of the Indonesian people.